The Effectiveness of the Family Hope Program (PKH) Social Assistance in Increasing the Welfare of Poor Communities - Hendrik Marantek; Hono Sejati (Publikasi Indonesia, 2023)
This study focuses on poverty and the efforts of the government in Indonesia to improve the welfare of the poor through the Family Hope Program (PKH). The research utilizes a qualitative descriptive method to examine the role of the government in providing assistance through PKH. The study highlights the various roles and skills required of PKH facilitators in their interactions with program beneficiaries. The government's role includes facilitative roles and skills, where PKH facilitators act as motivators and provide support in health services such as regular check-ups for pregnant women and children at local health centers. PKH facilitators also require educational roles and skills to effectively communicate information and conduct activities with the community. These educational roles are essential for increasing knowledge and raising awareness among program beneficiaries. Additionally, PKH facilitators need representative roles and skills to effectively convey information and feedback between beneficiaries and local government authorities. This role ensures that the voices and concerns of beneficiaries are heard and addressed by relevant stakeholders.